Influence of the bedding plane on the propagation of multiple hydraulic fractures - Ma, Yulin; Wang, Ding; Zheng, Yongxiang (Frontiers in Earth Science, 2023)
The presence of bedding planes (BPs) in unconventional shale reservoirs is common and widespread. BPs always affect fracture propagation. The objective of this study was to investigate the impacts of BPs on multiple hydraulic fracturing. The BPs were assumed to be perpendicular to the direction of the fractures. Based on the block distinct element method, we established a numerical model to simulate multiple fracture propagation in reservoirs with BPs. The model considered the fluid partitioning of multiple fractures and the fracture interaction by stress shadow. The numerical simulations clearly showed that the BPs reduced the non-uniform growth of multiple fractures. The results indicated that when hydraulic fractures met BPs, the BPs likely prevented the hydraulic fractures from passing through the formation with a smaller stress contrast. When hydraulic fracturing in a formation containing BPs, the key problem is how to reduce the obstructive effects of the BPs to increase the length of the main fractures.